1993
DOI: 10.1111/j.1529-8817.1993.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIABILITY OF GELIDIUM CANARIENSIS (RHODOPHYTA) DETERMINED BY ISOZYME ELECTROPHORESIS1

Abstract: The populations of Gelidium canariensis (Grunow) Seoane‐Camba from the Canary Islands were analyzed for genetic variability by isozyme electrophoresis in 1989 and 1990. Each population was divided into sporophytic and gametophytic subpopulations. Twenty‐three to 27 putative alleles corresponding to 22 gene loci were analyzed. Sev‐enteen loci were monomorphic in all six subpopulations, and five were polymorphic in at least one subpopulation. Significant deviations from Hardy‐Weinberg equilibrium were found. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…Narrow endemicity and insularity are poor predictors of RAPD variability in the seven surveyed stands of Gelidium canariense . Unlike allozymes (Sosa and García‐Reina 1993), RAPD detected high levels of gene diversity in all populations analyzed. Of all characteristics of an organism's life history, outcrossing and life forms in plants has been shown to have the most importance in determining levels of genetic variability.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Narrow endemicity and insularity are poor predictors of RAPD variability in the seven surveyed stands of Gelidium canariense . Unlike allozymes (Sosa and García‐Reina 1993), RAPD detected high levels of gene diversity in all populations analyzed. Of all characteristics of an organism's life history, outcrossing and life forms in plants has been shown to have the most importance in determining levels of genetic variability.…”
Section: Discussionmentioning
confidence: 77%
“…From a genetic point of view, natural populations of G. canariense have been studied by allozyme electrophoresis (Sosa and García‐Reina 1993). From the low genetic diversity detected and the existence of differences between gametophytic and tetrasporophytic allelic frequencies it was concluded that asexual reproduction constituted the predominant form of reproduction in the analyzed populations (Sosa and García‐Reina 1993). However, due to the low number of gametophytic individuals analyzed, a possible bias could have been present in this study.…”
mentioning
confidence: 99%
“…Oliveira, 1986 (Guillemin et al 2008). In other species, the occurrence of sex, even occasionally, explained the lack of significant differences between haploid and diploid subpopulations: Gelidium canariensis (Grunow) Seoane Camba (Sosa & Garcia-Reina 1993); Gracilaria gracilis (Stackhouse) M. Steentoft, L. M. Irvine and W. F. Farnham 1995 (Engel et al 2004); Cladophoropsis membranacea (Hofman Bang ex C.Agardh) Børgesen, 1905(van der Strate et al 2002, and Chondrus crispus Stackhouse, 1797 (Krueger-Hadfield et al 2011). Genotyping both haploid and diploid individuals in these species is necessary to detect clonality and its effect on population structure.…”
Section: Taxonomic Knowledgementioning
confidence: 99%
“…These results suggest interpopulation dispersal in E. cava is limited, compared to terrestrial plants, even though their biology and environments are completely different. In fact, seaweeds are generally considered poor dispersals because spore survival is generally limited to a few days (Santelices 1990, Sosa andGarcía-Reina 1993). The restricted gene flow in E. cava likely results from the limited long distance dispersal of spores, gametes, or drifting reproductive fragments.…”
Section: Discussionmentioning
confidence: 99%